Skin-contact actuated single-electrode protein triboelectric nanogenerator and strain sensor for biomechanical energy harvesting and motion sensing - Gogurla, Narendar; Roy, Biswajit; Park, Ji Yong; Kim, Sunghwan (Nano Energy, 2019)
Wearable/attachable electronics are essential for the seamless human-machine interface. However, it is still challenging to obtain an efficient and lighter power source. Here, we utilize a nanostructured silk protein and silver nanowires (AgNWs) buried in the silk nanostructure to yield an efficient, flexible, transparent, and skin/textile-compatible triboelectric nanogenerator (TENG) and strain sensor for biomechanical energy harvesting and motion sensing. As a strain sensor, the device shows very high gauge factor (~30), and stably detects the bending and unbending of knuckles. With the large surface area of the nanostructured silk/AgNW surface, finger-contact can actuate the silk bio-TENG and generate the considerably high power density of 2 mW/cm2, which is sufficient to power light-emitting diodes. The optical transparency of the bio-TENG makes it possible to use the device as a touch sensor on electronic devices. The strain sensor and the bio-TENG are integrated into a single silk chip and attached to skin and fabrics to monitor the strain and harvest the biomechanical energy at the same time. Advantages of the protein-based energy skin including low cost, ease of fabrication, biocompatibility, flexibility, and transparency, empower its usage for a seamless human-machine interface, touch sensor, and wearable bioelectronics.
Keywords: Flexible; High gauge factors; High power density; Human Machine Interface; Nanogenerator; Optical transparency; Silk proteins; Strain sensors; Flexible; Silk protein; Strain sensor; Triboelectric nanogenerator; Wearable electronics